Optimasi Parameter Proses Pembuatan Biobriket dari Campuran Tongkol Jagung dan Tempurung Kelapa menggunakan Metode Taguchi - Bagus Prabowo; Pondi Udianto (International Forum of Researchers and Lecturers, 2026)
The increasing global energy demand and dependence on fossil fuels have driven the development of renewable alternatives from agricultural waste. Corn cobs and coconut shells are abundant lignocellulosic biomass wastes in Indonesia that remain underutilized as biobriquette raw materials, and previous studies generally optimized only one or two process parameters separately. This study aims to determine the optimal combination of process parameters for producing high-quality biobriquettes from corn cobs and coconut shells that meet the Indonesian National Standard (SNI 01-6235-2000). An experimental approach applied the Taguchi Orthogonal Array L9(3⁴) integrated with Grey Relational Analysis (GRA) to simultaneously optimize four factors, namely shell to cob ratio, tapioca adhesive concentration, carbonization temperature, and particle size, against five quality characteristics: calorific value, moisture content, ash content, volatile matter, and fixed carbon. The optimal combination was a shell to cob ratio of 75:25, adhesive concentration of 5%, carbonization temperature of 500°C, and particle size of 60 mesh, producing the highest Grey Relational Grade of 0.8891, with raw material ratio as the most dominant factor. The confirmation experiment produced biobriquettes with a calorific value of 6,759 cal/g and other characteristics fully satisfying SNI 01-6235-2000, with a prediction error of 7.99%. These findings confirm that the Taguchi-GRA approach is effective for simultaneous multi-parameter, multi-response optimization of agricultural waste-based biobriquettes.